In vitro antifungal activity of hydroxychavicol isolated from Piper betle L - Afrin Farhat; Dutt Prabhu; Satti Naresh K; Gupta Bishan D; Suri Krishan A; Khan Farrah G; Ali Intzar; Qazi Ghulam N; Khan Inshad A (BMC, 2010)
Abstract Background Hydroxychavicol, isolated from the chloroform extraction of the aqueous leaf extract of Piper betle L., (Piperaceae) was investigated for its antifungal activity against 124 strains of selected fungi. The leaves of this plant have been long in use tropical countries for the preparation of traditional herbal remedies. Methods The minimum inhibitory concentration (MIC) and minimum fungicidal concentration (MFC) of hydroxychavicol were determined by using broth microdilution method following CLSI guidelines. Time kill curve studies, post-antifungal effects and mutation prevention concentrations were determined against Candida species and Aspergillus species "respectively". Hydroxychavicol was also tested for its potential to inhibit and reduce the formation of Candida albicans biofilms. The membrane permeability was measured by the uptake of propidium iodide. Results Hydroxychavicol exhibited inhibitory effect on fungal species of clinical significance, with the MICs ranging from 15.62 to 500 μg/ml for yeasts, 125 to 500 μg/ml for Aspergillus species, and 7.81 to 62.5 μg/ml for dermatophytes where as the MFCs were found to be similar or two fold greater than the MICs. There was concentration-dependent killing of Candida albicans and Candida glabrata up to 8 × MIC. Hydroxychavicol also exhibited an extended post antifungal effect of 6.25 to 8.70 h at 4 × MIC for Candida species and suppressed the emergence of mutants of the fungal species tested at 2 × to 8 × MIC concentration. Furthermore, it also inhibited the growth of biofilm generated by C. albicans and reduced the preformed biofilms. There was increased uptake of propidium iodide by C. albicans cells when exposed to hydroxychavicol thus indicating that the membrane disruption could be the probable mode of action of hydroxychavicol. Conclusions The antifungal activity exhibited by this compound warrants its use as an antifungal agent particularly for treating topical infections, as well as gargle mouthwash against oral Candida infections.